The last black man in San Francisco [videorecording (DVD)] - Talbot, Joe; Talbot, Joe; Talbot, Joe; Fails, Jimmie; Majors, Jonathan, 1989-; Glover, Danny (Lionsgate, 2019)
In San Francisco, a black man plots to get back his childhood home built by his grandfather, from which his family was forced out when the neighborhood became too expensive.